Analisa Penyebab Short Cargo pada Proses Pemuatan Batubara dari Area Open Stockpile - Niken D. Rosita; Hermawati Renny; Marini N. Sasa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
Coal Loading and unloading requires special handling, including the storage process. Storage can be done on a stacking field or called a stockpile. Each type of stockpile has advantages and disadvantages related to the quality and quantity of cargo. The stockpile in this study is an open stockpile. This study aims to describe the causes of short cargo in the open stockpile area. Short cargo is a condition where the cargo loaded or unloaded from and to the hatch is deficient and does not comply with the stowage plan. Short cargo is caused by various things including loading and unloading labor errors, insufficient jetty supervision, loading and unloading with cranes so that some cargo is spilled, stolen, spontaneous combustion and lost due to weather conditions. The loading process is carried out from the open stockpile into the MV hatch. Josco Nanjing V.123 and short cargo of 0.75% which is 1,074,059 MT from a total cargo of 41,574,059 MT. This research method uses qualitative research and data collection techniques through literature studies and observations in the field. The results of the study illustrate that the cause of short cargo in coal loading in MV. Josco Nanjing V.123 V.193 caused by wet cargo from open stockpile, lack of coal stock, coal spill when unloading to stockpile and human error in observation of ship drafts. The handling to minimize short cargo by drying before loading, planning a slicing system, improving crane operator expertise on the use of shore grabs and increasing surveyor's accuracy in related ship drafts